Talent screening identification instrument: prospective art & design students / Syahrini Shawalludin...[et al.] - Shawalludin, Syahrini; Mohamed Salim, Neesa Ameera; Mamat Nawi, Azmir; Md Hashim, Azhari (2019)
The Faculty of Art & Design, Universiti Teknologi MARA (UiTM) offers programs for Diploma, Undergraduate and Post Graduate wishing to pursue art and design studies. A total of nine programs are offered; Fine Arts, Graphic & Digital Media, Fashion, Industrial Design, Textile Design, Fine Metal, Ceramics, Fine Art and Printing Technology. To date, the student selection process will be selected through a screening process inclusive of an interview session, drawing test, and colour-blind test that is compulsory for entry into the following Diploma programs. The study argues how the current and past practice on screening traces and identifies the talent in art and design since the candidates have limited knowledge and exposure in the ten areas offered. Consequently, this also affects the interest, learning process, potential skills, and limits the career development if the wrong programs are offered to them. This study identifies a solution in identifying the relevant talent and aptitude in art and design. A total of 148 candidates were involved in this study. An instrument in a form of questionnaire were given to the candidates which provides a systematic criterion in determining if the candidate has interest and talent in the nine areas provided. This study focuses on the importance of the talent identification screening instrument to assess talent for potential students who plans to embark their studies under the Faculty of Art & Design in Universiti Teknologi MARA (UiTM). The study suggests and define the talent screening instrument is an added value to the talent identification process which has been justified relevant and beneficial to be implemented to the student selection process.